Desarrollo de las inteligencias múltiples para fortalecer el área cognitiva en niños de educación inicial - Torres Ruiz, Yasmirle Aurora (2021)
Multiple intelligences enhance cognitive processes at the information processing levels in infants. The benefits of using optimal techniques and strategies to stimulate toddlers from early childhood to ensure comprehensive development. Therefore, multiple intelligences have been identified as the independent variable, while the development of skills in the cognitive area has been designated as dependent. To achieve this, it is necessary to analyze the theoretical references that support the variables of the research, to obtain a bibliographic support, giving the project a reliable mixed approach of a descriptive type and a field modality……….